2014
DOI: 10.1017/s0272263114000333
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinguistic Differences in Implicit Language Learning

Abstract: We report three experiments that explore the effect of prior linguistic knowledge on implicit language learning. Native speakers of English from the United Kingdom and native speakers of Cantonese from Hong Kong participated in experiments that involved different learning materials. In Experiment 1, both participant groups showed evidence of learning a mapping between articles and noun animacy. In Experiment 2, neither group showed learning of a mapping between articles and a linguistically anomalous concept (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 25 publications
6
53
1
Order By: Relevance
“…We also recorded event-related brain potentials (ERPs) to provide additional measures of learning and rule awareness. We hypothesized that learning of the hidden rule should be evident in slower responses to phrases that violated the rule, similar to previous findings (Leung & Williams, 2012, in press). We additionally hypothesized that ERP differences would emerge between canonical and violation phrases as participants implicitly learned the hidden rule, representing a neural index of learning.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…We also recorded event-related brain potentials (ERPs) to provide additional measures of learning and rule awareness. We hypothesized that learning of the hidden rule should be evident in slower responses to phrases that violated the rule, similar to previous findings (Leung & Williams, 2012, in press). We additionally hypothesized that ERP differences would emerge between canonical and violation phrases as participants implicitly learned the hidden rule, representing a neural index of learning.…”
Section: Introductionsupporting
confidence: 77%
“…For example, Leung and Williams (2011) found RT evidence for implicit learning of mappings between novel articles and thematic role (i.e., whether a noun is an agent or patient). Similarly, using a paradigm that provided the methodological basis for the present study, Leung and Williams (2012; in press) found RT delays to phrases that violated a hidden noun animacy rule, providing evidence for implicit learning of associations between forms and animacy.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations